Glycaemic control in transition‐aged versus early adults with type 1 diabetes and the effect of a government‐funded insulin pump programme. Issue 11 (16th June 2021) - Mooney, Shane P.; Booth, Gillian L.; Shulman, Rayzel; Na, Yingbo; Weisman, Alanna; Shah, Baiju R.; Perkins, Bruce A.; Lipscombe, Lorraine
Abstract: Aim: To compare glycaemic control and adverse outcomes between transition‐aged and early adults with type 1 diabetes, and the impact of continuous subcutaneous insulin infusion (CSII) therapy funded through a government Assisted Devices Program. Methods: This retrospective cohort study using healthcare administrative databases from Ontario, Canada included adults aged 18–35 with type 1 diabetes between 1 April 2011 and 31 March 2014. Mean HbA1c was compared between transition‐aged (18–24 years) and early adults (25–35 years), overall and stratified by whether or not they received government‐funded CSII therapy (CSII vs. non‐CSII). Secondary outcomes included rates of hospitalizations/emergency department visits for hyperglycaemia and hypoglycaemia over a 3‐year follow‐up. Comparisons were adjusted for relevant covariates. Results: Among 7157 participants with type 1 diabetes, mean HbA1c was significantly higher for transition‐aged compared to early adults (71 mmol/mol [8.68%] vs. 64 mmol/mol [8.04%], p < 0.0001). This difference was smaller among CSII compared to non‐CSII users ( p = 0.02 for interaction between age group and CSII use). The transition‐age group were more likely to experience a hyperglycaemic event compared to early adults (adjusted risk ratio, aRR: 1.56, 95% confidence interval [CI]: 1.25–1.96), which was attenuated by CSII use (aRR: 1.13, 95% CI: 0.7–1.69). Conclusions: Transition‐aged adults with type 1 diabetes had a significantly higher mean HbA1c and risk of hyperglycaemic events compared to early adults. This difference was attenuated for CSII users, indicating that a government‐funded CSII programme is associated with narrowing of the gap in glycaemic control and associated adverse outcomes for this population.